L’apport des compagnies d’assurance-vie au développement économique du Québec - Moffet, Denis (Assurances)

(untitled) (HEC Montréal, 1993)
The author shows that the liberalization of Life insurance companies investments made possible by Bill 75 passed in 1984, is part of a long term movement closely associated to the so-called quiet revolution initiated at the beginning of the '60s and aiming at promoting the economic development of Québec. A glance at statistics pertaining to the period 1984-90, unveils that the growth in assets was not adequately matched by profitability and capitalization. The author concludes that Life insurance companies should mainly concentrate on their fiduciary role and contribute in an accessory manner to the economic development of Québec.